Penggunaan, Efektivitas Efektivitas Games-Based Learning Dalam Meningkatkan Kemampuan Qowaidul Imla’ Di Salafiyyah Ula Tahfizh Ummul Quro - Suprapto, Luthfia; Resy Mulyani (Journal of Practice Learning and Educational Development, 2026)
This study aimed to determine the effectiveness of Game-Based Learning in improving Qowaidul Imla’ ability among students at Salafiyyah Ula Tahfizh Ummul Quro. The study was motivated by the low ability of students to understand and apply Arabic writing rules, as well as the need for innovative learning strategies that can increase student engagement and learning outcomes. This research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design. The sample consisted of 37 students, divided into an experimental class and a control class selected through purposive sampling. Data were collected through tests, observation, and documentation and analyzed using normality tests, homogeneity tests, and Independent Sample t-Test with the assistance of SPSS software. The results showed that the data were normally distributed and homogeneous, with Shapiro-Wilk significance values of 0.107 for the pretest and 0.106 for the posttest, while Levene’s Test significance values were 0.113 and 0.076, respectively. The Independent Sample t-Test yielded a significance value of 0.015 (p < 0.05), indicating a significant difference between the experimental and control groups. Therefore, Game-Based Learning was found to be effective in improving students’ Qowaidul Imla’ ability at Salafiyyah Ula Tahfizh Ummul Quro.